Membangun Bilik Asmara Melalui Keadilan Substantif - Untung Sumarwan (Deviance Jurnal kriminologi, 2017)
Overcapacity in Indonesian correctional institutions has still become an issue. Inmates’ or prisoner’s sexual needs that has been accommodated through conjugal visit has also still become a problem. Sex is human rights, a rights that is inherent in the nature of human being. It cannot be substituted, and is entitled to anyone—disregarding the fact whether one is a free person, a slave, or living in prison. This rights has been emphasized as well in the 1948 United Nations Declaration as part of human rights. Indonesia, as a member of the United Nations, should obey the declaration. However, the mean to fulfill the human rights in correctional institution have not yet existed until today. The absence of it could trigger other problems. The correctional institution may be prone to suffer from riots, and behavior deviances. These problems may occur at the level of individual or institution. In addition to those, it is evident that there are cases that lead to suspicion on motive of economy profit.